1987
DOI: 10.1104/pp.83.2.360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drought on Primary Photosynthetic Processes of Cotton Leaves

Abstract: The effects of drought on Photosystem II (PSII) fluorescence and photosynthetic electron transport activities were analyzed in cotton. Water stress did not modify the amplitude of leaf variable fluorescence at room temperature in the presence of 343,4-dichlorophenyl)-1,1-dimethylurea (DCMU) nor at 77 K. It is therefore concluded that photon collection, their distribution between the two photosystems, and PSII photochemistry are unaffected by the stress. In droughted leaves at room temperature under low excitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
77
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(93 citation statements)
references
References 15 publications
12
77
2
Order By: Relevance
“…Although the F v : F m values obtained at midday were slightly smaller than those obtained at predawn (0.75 vs 0.80), the maintenance of constant F v : F m values at midday throughout the experiment demonstrates the lack of drought-induced damage to PSII photochemistry, as already reported for many species (Genty et al, 1987 ;Cornic, 1994). This was accompanied by a decrease in chlorophyll, but also by an increase in the ratio Car : Chl, which partly explains the absence of drought-induced damage to PSII (Demmig-Adams & Adams III, 1996).…”
Section: mentioning
confidence: 59%
“…Although the F v : F m values obtained at midday were slightly smaller than those obtained at predawn (0.75 vs 0.80), the maintenance of constant F v : F m values at midday throughout the experiment demonstrates the lack of drought-induced damage to PSII photochemistry, as already reported for many species (Genty et al, 1987 ;Cornic, 1994). This was accompanied by a decrease in chlorophyll, but also by an increase in the ratio Car : Chl, which partly explains the absence of drought-induced damage to PSII (Demmig-Adams & Adams III, 1996).…”
Section: mentioning
confidence: 59%
“…3,24). In contradiction, Genty et al (12) concluded that PSI-mediated electron transport was inhibited by drought, whereas PSII electron transport remained the same. They also reported that drought does not induce sensitization to photoinhibition.…”
Section: Discussionmentioning
confidence: 83%
“…Several mechanisms of protection against high irradiance occur at different levels (18 The mechanism by which drought stress inhibits the photosynthetic electron transport system is still unclear, although a number of authors have attempted an explanation (3,12,15,17,26). Ogren and Oquist (24) concluded from their results that the drought-induced decline in CO2 uptake was initially equally attributable to stomatal and nonstomatal factors, but the further decline as drought continued was solely due to nonstomatal factors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…After 5 days of re-watering, gas exchange parameters did not show a complete recovery may be due to limitation of stomatal and mesophyll conductance and biochemical limitations . In many species, PSII is quite resistant to drought (GENTY et al, 1987;CORNIC et al, 1992). Maximum quantum yield of PSII (Fv/Fm) did not change significantly under moderate drought stress in both clones, indicating no photodamage to PSII reaction centers (FOYER et al, 1994).…”
Section: Discussionmentioning
confidence: 99%